EVALUATION OF QUALITY OF LIFE IN LUNG CANCER PATIENTS - MANNARINO, Vera Lucia; BONIOLI, Gisele Cazale; NASCIMENTO, Emilia Matos do; PEREIRA, Basilio de Bragança; MELLO, Fernanda Carvalho de Queiroz; PASCHOAL, Marcos Eduardo Machado (Brazilian Journal of Biometrics, 2022)
There is a growing need to improve end-of-life care in cancer patients and to evaluate it through questionnaires is an important tool to assess its results. The aim of this study was to evaluate the effect of the palliative care in the quality of life, distressing symptoms and functional capacity of patients with primary lung cancer with locally advanced disease and metastatic disease in a university hospital. Thirty patients with lung cancer, previously treated with curative intention and submitted to a palliative treatment, were enrolled for this study. They were divided into three groups. The first group had 10 patients, who lived between 30 and 59 days after admittance, the second, 10 patients who lived between 60 and 89 days and the third, 10 patients who lived 90 days or more. Data collection regarding five stressing symptoms: anorexia, dyspnea, pain, fatigue, hemoptysis, and cough, was performed according to Lung Cancer Symptom Scale and Karnofsky Performance Status Scale. By observational inspection, “Appetite” and “Karnofsky Performance Status Scale”, improved; “pain" worsened and "quality of life" improved after palliative care, according to the patients. Physical, psychological, spiritual and social factors influence the symptoms of patients with cancer in later life. Treatment by palliative care can provide comfort for these patients.